Examination of agility performances of soccer players according to their playing positions - Goral, K. (The Sport Journal, 2015)
The aim of this study was to examine of agility performances according to soccer players` playing positions. Sixty-eight soccer players (age: 23.76 ± 2.79 years; height: 178.09 ± 4.80 cm; body weight: 74.15 ± 4.39 kg; body mass index: 23.37 ± 0.85) were tested for agility performance using the Illinois agility test and Agility-T test after warm up completion. The players were divided into 4 subgroups (goalkeepers, defenders, midfielders and strikers) according to their self-reported best position on the field. The analysis of the data obtained from the study was saved in SPSS version 16.0. First, the means and standard deviations were calculated for all variables. Then, the differences between soccer players from different groups were examined by One-way Analysis of Variance (ANOVA). The Tukey HSD test procedures were used to determine where differences existed. The level of significance was set at p0.05). The statistical analysis revealed that the Illinois agility test was significantly lower in the midfielders compared with the goalkeepers (p<0.05) and strikers (p<0.05). Also, there is no difference between goalkeepers and defenders (p>0.05). According to the results of The Agility T-test, midfielders were found to be significantly faster than the goalkeepers (p<0.05), but no difference were detected between other positions (p>0.05). In this study, the midfielders had the fastest agility values. Goalkeepers are slower than the other players` positions. In regard to the conclusion of this study, to measure and report the agility performances of players at regular intervals can provide significant benefits in the process of training to improve the performance levels of athletes playing in different positions.